School counselor leadership skills development: A systematic literature review - Yulizar, Yulizar; Ahman, Ahman; Nurihsan, Juntika; Saripah, Ipah (ProGCouns: Journal of Professionals in Guidance and Counseling, 2023)
Studies about school counselor leadership skills development shows diverse findings. Therefore, a comprehensive review of the emerging literature is required. This study utilized a systematic literature review in order to assess existing understanding about the school counselor leadership skill development. This research adhered to the Standard Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA-P) to collect 15 articles in accordance with the inclusion criteria. This article describes the context of leadership skill development among school counselors over the last ten years and measurement methods used in previous studies. It identifies possible contexts for developing future school counselor leadership skills. The research results are expected to provide insights for research designs in the future, so that they can formulate a framework for developing school counselor leadership skills that are meaningful and useful for improving the counseling profession. The findings of this research offer straightforward access to the recent state of research about school counselor leadership skills development. Some recommendations for research in the future are1) leadership skills development that can be carried out at the doctoral level; 2) considering emotional intelligence in the preparation of intervention programs; and 3) developinhg the cultural and environmental context of the school counselors.